2019
DOI: 10.2147/ccide.s204433
|View full text |Cite
|
Sign up to set email alerts
|

<p>Prevalence of work-related musculoskeletal disorders and ergonomic practice among dentists in Jeddah, Saudi Arabia</p>

Abstract: Background Musculoskeletal disorders (MSD) is the second most common cause of disability. MSD due to the occupation are called work-related musculoskeletal disorders (WMSD) and are common among dentists. Objective Assess the prevalence of self-reported work-related musculoskeletal disorders (WMSD) and to identify associated ergonomic practice among dentists practicing in Jeddah City, Saudi Arabia. Methods Dentists practicing in Jeddah were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
61
2
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(79 citation statements)
references
References 29 publications
10
61
2
6
Order By: Relevance
“…However, no significant differences were observed in back pain intensity between both genders. Although this result is consistent with the study conducted by Ferguson et al [ 35 ] among manual material handling workers in the United States, recent studies have reported a higher LBP prevalence in women [ 3 , 9 , 34 ]. Therefore, it would be very useful to clarify the real impact of the gender factor on LBP in future research.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…However, no significant differences were observed in back pain intensity between both genders. Although this result is consistent with the study conducted by Ferguson et al [ 35 ] among manual material handling workers in the United States, recent studies have reported a higher LBP prevalence in women [ 3 , 9 , 34 ]. Therefore, it would be very useful to clarify the real impact of the gender factor on LBP in future research.…”
Section: Discussionsupporting
confidence: 93%
“…According to this study’s results, it was also possible to verify that the most common musculoskeletal pain area was the low back, followed by the neck. This result coincides with most of the existing studies conducted in Saudi Arabia that were related to musculoskeletal disorders [ 3 , 30 , 31 , 34 ]. However, this result was slightly different from the results found by Sirajudeen et al [ 29 ] since they observed that the neck was the most common pain area, followed by the low back.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations